Impacts of Macleaya cordata on Productive Performance, Expression of Growth-Related Genes, Hematological, and Biochemical Parameters in Turkey - Manaa, Eman A.; Abdel-Latif, Mervat A.; Ibraheim, Samya E.; Sakr, Abdelaziz; Dawood, Mahmoud; Albadrani, Ghadeer M.; El-kott, Attalla F.; Abdel-Daim, Mohamed M.; Shafik, Basant M. (Frontiers in Veterinary Science, 2022)
Macleaya cordata is a herbal plant that has abundant amounts of sanguinarine which has many biomedical properties. Impacts of Macleaya cordata dietary supplementation on the productive performance, some blood constituents, and growth-related genesˈ expression were evaluated in turkey. Macleaya cordata extract was dietary supplemented to turkey at levels of 25, 50, and 100 ppm, and a control group. Growth performance measurements (FBW, ADG, and FCR) and production efficiency factor for turkey (BPEF) were similar (p ˃ 0.05) in all supplemented groups. Macleaya cordata has no adverse effects (p ˃ 0.05) on the birds' health regarding hematological (Hb, RBCs, WBCs, and PCV) and blood biochemical indices evaluating liver function, kidney function and lipid profile. Moreover, the mRNA expression of growth related genes like growth hormone receptor (GHR), insulin like growth factor 1 (IGF-1), adenine nucleotide translocase (ANT), cyclooxygenase 3 (COX-3) and uncoupling protein 3 (UCP-3) were upregulated (p < 0.001) in Macleaya cordata treatments with the highest value for SG50 compared to control group. We concluded that, exogenous Macleaya cordata dietary supplementation, upregulated the expression of growth- related genes in turkey at a level up to 50 ppm without adverse effects on their heath status.